Rigid wing sailboats: A state of the art survey. (1st September 2019) - Silva, Manuel F.; Friebe, Anna; Malheiro, Benedita; Guedes, Pedro; Ferreira, Paulo; Waller, Matias
Abstract: The design, development and deployment of autonomous sustainable ocean platforms for exploration and monitoring can provide researchers and decision makers with valuable data, trends and insights into the largest ecosystem on Earth. Although these outcomes can be used to prevent, identify and minimise problems, as well as to drive multiple market sectors, the design and development of such platforms remains an open challenge. In particular, energy efficiency, control and robustness are major concerns with implications for autonomy and sustainability. Rigid wingsails allow autonomous boats to navigate with increased autonomy due to lower power consumption and increased robustness as a result of mechanically simpler control compared to traditional sails. These platforms are currently the subject of deep interest, but several important research problems remain open. In order to foster dissemination and identify future trends, this paper presents a survey of the latest developments in the field of rigid wing sailboats, describing the main academic and commercial solutions both in terms of hardware and software.